Is Ruggedness a Key Habitat Feature for Woodland Caribou Along the Lake Superior Coast? - McClinchey, Jack (2018)
Woodland caribou (Rangifer tarandus caribou Gmelin) in the Lake Superior Coast Range are at risk, having been extirpated in portions of their range including Lake Superior Provincial Park and Pukaskwa National Park (PNP). A resource selection function has yet to be formulated for this population. I chose to examine the population between Terrace Bay and Marathon, Ontario, where the most recent observations of mainland individuals has occurred, hypothesizing that rugged terrain was a mechanism for caribou to escape predation from wolves (Canis lupis L.). These animals do not appear to use rugged terrain, as they were found to be spaced away from rugged areas. Ruggedness is likely important at the landscape scale, segregating caribou from moose (Alces alces L.) and consequently wolves. At the finer scale caribou probably avoid rugged terrain to lower energetic costs. Alternatively, refuge islands appear to act as the primary means of spatial segregation between caribou, moose and wolves. Heavy selection for these features is not a viable long-term survival strategy for caribou in the LSCR, as shown by an extirpated population in PNP. I suggest that caribou will be extirpated from the LSCR, as populations on Michipicoten and Slates Islands which have likely sourced the mainland coast have recently become extirpated or nearly so.